Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(a+b\right)\left(c-d\right)-\left(a-b\right)\left(c+d\right)\)
\(=\left(ac-ab+bc-bd\right)-\left(ac+ad-bc-bd\right)\)
\(=ac-ad+bc-bd-ac-ad+bc+bd\)
\(=2bc-2ad\)
\(=2\left(bc-ad\right)\)
- (a + b - c) + (b - c + d) - (-a + b + d)
= -a -b + c + b - c + d + a - b - d
= -b
1) -a(-a+c-d)-(c-a+d)
=ad-ac+a2-c+a-d
2) -(a+b)-(c+d)+(a-b-c-d)
=-a-b-c-d+a-b-c-d
=-2b-2c-2d
3) a(b-c-a)-a(b+c-d)
=-ac+ab-a2+ad-ac-ab
=ad-2ac-a2
-(a+b-c+d)+(a-b-c-d)=-a-b+c-d+a-b-c-d=(-a+a)-(b+b)+(c-c)-(d+d)=0-2b+0-2d=-2b+(-2)d=-2(b+d)
-(a+b-c+d)+(a-b-c-d)
= -a-b+c-d+a-b-c-d
= -2b-2d
Nhấn đúng cho mk nha!!!!!!!!!!!
a, -( -a + c - d) - ( c - d + d) = a - c + d - c + d - d = a + d
b, - ( a+b-c+d) + (a-b-c-d) = -a -b+c-d + a-b-c-d = -2b + (-2c)= -2(b+c)
a(b-c-d)-a(b+c-d)=a(b-c-d-b+c-d)=a[(b-b)-(c-c)-(d+d)]=2[0-2d]=2*(-2d)=2(1+d)